EFFECT OF SIMVASTATIN ON HISTOPATHOLOGY OF THE HEART AFTER 5/6 SUBTOTAL NEPHRECTOMY - CAHYAWATI, PUTU NITA (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aims to assess the condition of cardiac histopathology through hematoxylin-eosin staining in 5/6 subtotal nephrectomy conditions. Methods: Fifteen male Swiss mice aged 3–5 months will be grouped into 3 treatment groups, namely the nephrectomy group (JSN, n=5), sham operation (JSO, n=5), and simvastatin 20 mg/kg body weight (JSIM, n=5). The histopathology of the heart will be assessed blindly. Severity is assessed based on scoring using a scale (−) no damage, (+) mild, (++) medium, and (+++) heavy. Assessment of severity refers to the irregularity of the heart muscle, increased amount of connective tissue, myofibril hypertrophy, myofibril swelling, sarcoplasmic fragmentation, sarcoplasmic vacuolization, bleeding in a myofibril, myofibril degeneration, cardiomyocyte damage, and the presence of acidophilic cytoplasm. Results: The results showed no morphological changes in heart muscle tissue in the JSO group except for fragmentation and vacuolization in minimal amounts of sarcoplasm (+), whereas in the JSN and JSIM groups, there was moderate damage to sarcoplasm (++) and minimal changes in myofibrils (hypertrophy and bleeding) (+). The JSN group also found severe damage (+++) to the irregularity of the heart muscle, whereas in JSIM, only moderate damage was found (++) to the irregularity of the heart muscle. Conclusion: Simvastatin seems to be able to correct the irregularity of the heart muscle in the condition of 5/6 subtotal nephrectomy.